Altered White Matter Microstructures in Type 2 Diabetes Mellitus: A Coordinate‐Based Meta‐Analysis of Diffusion Tensor Imaging Studies - Zhou, Cong; Li, Jie; Dong, Man; Ping, Liangliang; Lin, Hao; Wang, Yuxin; Wang, Shuting; Gao, Shuo; Yu, Ge; Cheng, Yuqi; Xu, Xiufeng (Frontiers in Endocrinology, 2021)
Objective: Type 2 diabetes mellitus (T2DM) is often accompanied by cognitive decline and depressive symptoms. Numerous diffusion tensor imaging (DTI) studies revealed microstructural white matter (WM) abnormalities in T2DM but the findings were inconsistent. The present study aimed to conduct a coordinate‐based meta‐analysis (CBMA) to identify statistical consensus of DTI studies in T2DM. Methods: We performed a systematic search on relevant studies that reported fractional anisotropy (FA) differences between T2DM patients and healthy controls (HC). The anisotropic effect size seed‐based d mapping (AES-SDM) approach was used to explore WM alterations in T2DM. A meta‐regression was then used to analyze potential influences of sample characteristics on regional FA changes. Results: A total of 8 studies that comprised 245 patients and 200 HC, along with 52 coordinates were extracted. The meta‐analysis identified FA reductions in three clusters including the left inferior network, the corpus callosum (CC) and the left olfactory cortex. Besides, FA in the CC was negatively correlated with body mass index (BMI) in the patients group. Conclusions: T2DM could lead to subtle WM microstructural alterations, which might be associated with cognitive deficits or emotional distress symptoms. This provides a better understanding of the pathophysiology of neurodegeneration and complications in T2DM.